The Real Exchange Rate and Growth in Zimbabwe: Does the Currency Regime Matter? - Zuzana Brixiova; Mthuli Ncube (Institute for the Study of Labor (IZA), 2014)
Zimbabwe faces growth and external competitiveness challenges, as indicated by its low trend growth and investment, declining share in the world exports, high current account deficits, and external debt. The stock-flow approach to the equilibrium exchange rate reveals that the real exchange rate experienced periods of sizeable overvaluation, both prior to the 2008 economic collapse and under the current multicurrency regime. While overvaluation hampers GDP growth, as well as growth and employment in export sectors, we have not found that undervaluation would raise it. Replacing the multicurrency regime anchored in the US by the South African rand as the sole transaction currency would help reduce overvaluation and stimulate exports and growth. Under any currency regime, Zimbabwe needs to adhere to sound macroeconomic policies, avoid overspending on public wages, and create environment conducive for investment.
Keywords: F36; F41; C22; O11; 330; real exchange rate misalignment; growth; employment; currency regime; Zimbabwe